Environmental Strategy and Investor Response: The Role of Green Innovation, Green Strategy and Carbon Strategy in Determining Cumulative Abnormal Returns - Fitriani, Ursulah Diana; Handoko, Jesica (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Abstract Purpose: Environmental concern can enhance a company’s competitive advantage and reputation, influencing investor assessments. In Indonesia, rising carbon emissions and stakeholder pressure encourage firms to adopt green innovation and carbon strategies to reduce environmental impact, increase corporate value, and affect market reactions. Methodology/approach: This study is quantitative, and purpose to analyze the factors that influence cumulative abnormal return (CAR). The independent variables are green innovation, green strategy, and carbon strategy, while firm size and profitability are used as control variables. Secondary Data were collected from IDX-listed energy, automotive, and transportation companies during 2021–2024. The sample was selected using purposive sampling and analyzed using multiple linear regression via SPSS 30. Findings: The results indicate that green innovation has influence on CAR, green innovation is able to create a high level of competitiveness for firms through productivity optimization and cost efficiency. Likewise, green strategy does not influence on CAR, because investors do not yet fully value or understand it as a source of long-term financial value. In contrast, carbon strategy positively influences CAR, companies proactively implementing carbon strategy are viewed as better prepared for future carbon emissions regulation and, more capable of managing environmental risk. Practical implications: Sustainability requires significant investment in human and financial resources, with benefits that are indirect and often only visible in the long term. Originality/Value: The government as a regulator needs to require public companies in Indonesia to implement sustainability strategies to support sustainable development.